Unsettling Encounters: A response to Katrin Flikschuh’s ‘Kant’s Nomads - Madore, Joël (Con-Textos Kantianos. International Journal of Philosophy, 2017)
In her thought-provoking article: “Kant’s Nomads: Encountering Strangers”, Katrin Flikschuh pursues three aims: I- to loosen the noose of the Kantian duty of state entrance against the repeated allegations of its inflexible universality; II- to rescue Kant from a certain “belligerent” liberal discourse that has overlooked his ambivalence on the question, at the expense of his potentially constructive insights; III- to articulate the possibility of an encounter with deep and permanent differences in culture or a “reflexive openness” that can help us face the “culturally unfamiliar”. Its success relies upon reading Kant’s philosophy as proceeding from a first-personal experiential standpoint, that is, a regressive strategy of justification. Though sympathetic to Flikschuh’s project, this paper wishes to examine to what extent it is compatible with the Kantian theory of the State, on the one hand, and his transcendental idealism, on the other. In the end, it may be that Kant’s openness to the other (i.e. the nomad), however sincere, remains transitory at best.
Keywords: Kant; cosmopolitanism; hospitality; nomads; cultural difference; State; anthropology.